Analytical and experimental evaluation of flexural behavior of FRP pultruded composite profiles for bridge deck structural design. (30th September 2017) - Xin, Haohui; Mosallam, Ayman; Liu, Yuqing; Wang, Congzhe; Zhang, Youyou
Highlights: A method to evaluate fiber volume fractions and equivalent thickness of lamina. Flexural characteristics of the pultruded deck were experimentally investigated. Finite element models considering laminates' and adhesives' failure were developed. Abstract: This paper presents a summary of a study that focuses on assessing flexural behavior of pultruded glass-fiber-reinforced polymer (GFRP) composite profiles commonly used in bridge deck applications. In this paper, a practical method to evaluate fiber volume fractions and equivalent lamina thickness is proposed. The elastic engineering constants of each laminate were predicted based on both micromechanics and classical laminate theory ( CLT ) and analytical results were verified using experimental results. Results confirmed the validity of the proposed methodology for predicting laminate elastic properties. A pultruded composite bridge deck profile, with double cells, was designed and manufactured from fiber/resin level to structural system level and both longitudinal and transverse flexural behaviors were experimentally and theoretically investigated. Experimental results including the location of the neutral axis, longitudinal and transverse bending and shear stiffness agreed well with theoretical results obtained from the proposed methodology presented in this paper. Finite element models considering the laminate damage based on Hashin's theory and adhesive layers' failure by using cohesive element were built and compared to the four-point bending experiments. Numerical displacements, strains, ultimate capacity and failure modes agreed well with experimental results.